PENGARUH GOOD CORPORATE GOVERNANCE, PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI) - B51111072, Justine (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
The purpose of this study was to determine the effect of good corporate governance in which there is a board of directors, independent directors and audit committee as well as profitability and leverage on firm value. The population in this study is as much as 45 property and real estate companies listed on the Stock Exchange from 2011-2013. With purposive sampling technique, the number of samples obtained are 15 companies. Data analysis methods used in this research is multiple linear analysis. The results showed that simultaneous good corporate governance, profitability and leverage no significant effect on the value of the company. Results of t-test showed that partially good corporate governance and leverage no significant effect on the value of the company, while profitability significantly influence the value of the company. Keywords: number of board of directors, the number of independent directors, the number of audit committee, corporate governance, profitability, leverage, the value of the company